Nurses' experiences of communication during the coronavirus disease 2019 pandemic: A qualitative study - Zahra Khademi; Elham Imani; Mohamad Heydari Khormizi (Shahrekord University of Medical Sciences, 2021)
Background and aims: Effective communication is a key to quality nursing care delivery. However, the necessity to wear personal protective equipment and keep physical distancing during the coronavirus disease 2019 (COVID-19) pandemic has created numerous challenges in establishing effective communication in healthcare settings. The aim of this study was to qualitatively explore nurses' experiences of communication during the COVID-19 pandemic. Methods: This qualitative study was conducted in 2020 using the Van Manen's hermeneutic or interpretational phenomenological design. Participants were thirteen nurses purposively selected from the COVID-19 care ward of a teaching hospital in Bandar Abbas, Iran. Data were collected through semi-structured interviews and were analyzed using the Van Manen's approach to phenomenological research. Results: Most participants were female (69.2%) and had bachelor's degree (84.6%). The means of their age and work experience were 32.08±5.42 and 9.54±5.22 years, respectively. A total of 1312 codes were generated during data analysis, which were grouped into 28 subcategories, thirteen categories, and the four themes of being in dire straits, social life disturbances, disturbance of peace, and ray of hope. Conclusion: The COVID-19 pandemic has challenged nurses' communication and hence, they need emotional and psychological support to remain hopeful. Nursing managers need to support nurses and remove barriers to their effective communication in order to enable them to provide safe and quality care.